Regulation of Commissureless by the ubiquitin ligase DNedd4 is required for neuromuscular synaptogenesis in Drosophila melanogaster. - Ing, B.; Shteiman-Kotler, A.; Castelli, M.L.; Henry, P.; Pak, Y.; Stewart, B.; Boulianne, G.L.; Rotin, D. (Molecular and Cellular Biology, 2007)
Muscle synaptogenesis in Drosophila melanogaster requires endocytosis of Commissureless (Comm), a binding partner for the ubiquitin ligase dNedd4. We investigated whether dNedd4 and ubiquitination mediate this process. Here we show that Comm is expressed in intracellular vesicles in the muscle, whereas Comm bearing mutations in the two PY motifs (L/PPXY) responsible for dNedd4 binding [Comm(2PY-->AY)], or bearing Lys-->Arg mutations in all Lys residues that serve as ubiquitin acceptor sites [Comm(10K-->R)], localize to the muscle surface, suggesting they cannot endocytose. Accordingly, aberrant muscle innervation is observed in the Comm(2PY-->AY) and Comm(10K-->R) mutants expressed early in muscle development. Similar muscle surface accumulation of Comm and innervation defects are observed when dNedd4 is knocked down by double-stranded RNA interference in the muscle, in dNedd4 heterozygote larvae, or in muscles overexpressing catalytically inactive dNedd4. Expression of the Comm mutants fused to a single ubiquitin that cannot be polyubiquitinated and mimics monoubiquitination [Comm(2PY-->AY)-monoUb or Comm(10K-->R)-monoUb] prevents the defects in both Comm endocytosis and synaptogenesis, suggesting that monoubiquitination is sufficient for Comm endocytosis in muscles. Expression of the Comm mutants later in muscle development, after synaptic innervation, has no effect. These results demonstrate that dNedd4 and ubiquitination are required for Commissureless endocytosis and proper neuromuscular synaptogenesis.